Smart Electricity Meter Reliable Life Prediction Based on Harmonic Factor. Issue 13 (9th August 2022) - Zhou, Mengxia; Zhao, Yang; Li, Qun; Liu, Xingfa; Wang, Yonan; Sun, Yiqun; Zhang, Cheng; Yan, Wei
Abstract: —The smart electricity meter (SEM) is a critical element of the smart grid, so power supply company and customers pay many attentions to its service life. SEM is directly employed in the power grid, and there is serious harmonic pollution. The traditional life prediction method of SEM has not considered the influence of the harmonic factor on the reliable life of the SEM, this paper proposes a novel life prediction method of SEM based on the harmonic factor. Based on the data of reliability harmonic test, the harmonic factor is extracted and integrated into the meter life prediction model to improve the accuracy of the prediction. The comparison between the prediction of multiple models of SEMs and the results of accelerated life testing verifies that the method has high accuracy.